Implementasi Tanda Tangan Digital Berbasis Ethereum Wallet dan Smart Contract untuk Sertifikat Elektronik HIMATIF - Zainul Muhaimin (Fakultas Ilmu Komputer, 2026)
This study designs and evaluates a blockchain-enabled signature and verification scheme for Himatif electronic certificates using a hybrid approach: off-chain signing through an Ethereum wallet and on-chain verification through a smart contract. The system is implemented as a single-page web application that runs fully client-side in the browser without an application server. Certificate integrity is protected by hashing the PDF content, embedding a metadata and QR code as a verification payload, and validating the signer, document hash, and metadata via a smart contract on the Sepolia Ethereum test network. A quantitative applied-science experiment was conducted using 88 certificates sampled from a population of 720 certificates with proportionate stratified random sampling. Functional testing covers the baseline certificate and multiple tampering scenarios, including PDF visual changes and post-sign edits, signer substitution using an unregistered address, and QR payload modification. Operational testing compares the hybrid approach against a full on-chain approach (sign and verify) in terms of execution time and gas-related costs. The functional results show that only the baseline certificate is verified as valid, while all manipulated variants are rejected. Performance results indicate that the hybrid approach reduces signing time (mean: 0.843s compared to 2.446s), reflected by non-overlapping 95% confidence intervals relative to the full on-chain approach, while verification times exhibit overlapping confidence intervals. In terms of fees, the full on-chain approach incurred a total of 0.00002268930853 SepoliaETH for 88 tests (0.0000002578330515 SepoliaETH per test), whereas the hybrid approach eliminates signing fees and performs verification through read-only calls. Overall, the proposed scheme provides practical integrity assurance for Himatif certificates and demonstrates the potential for broader adoption in faculty-level document verification systems.
Implementation of Ethereum Wallet and Smart Contract Based Digital Signatures for Himatif Electronic Certificates
Validasi dan Finalisasi Repositori File 20 Juli 2026_Kholif Basri
Keywords: Blockchain; Ethereum Wallet; Smart Contract; Electronic Certificate; Hybrid Signature